Frequency of Transition of patients with NYHA class III / IV to NYHA class I / II / III of stage C and D Heart Failure with Pharmacotherapy in a Tertiary Level Hospital - Ansari, Sanjida; Kabir, Md Faisal Ibn; Ahmed, Khurshed; Ahsan, Syed Ali; Ahmed, Chaudhary Meskat; Khaled, Md Fakhrul Islam; Siraj, Mausool; Nahar, Jannatun; Biswas, Sumon Kumar; Karna, Rajan; et al. (University Heart Journal, 2022)
Background: Heart failure (HF) is one of the most important health problems in terms of prevalence, morbidity, mortality and health service use. It affects around 2 to 3 % of the population. NYHA class can be used for the prioritization, triage and tailoring the HF management which is the foundation for the selection of therapies. The patient with higher NYHA class may need Mechanical Circulatory Support therapy or palliative care or hospice care. The identification of the patients with lower NYHA class helps to tailor vigorous drug therapy and close follow up program, the prognosis of these low risk patients maybe further improved. It is a simple tool for risk stratification in clinical practice. Objective: The principal objective of this study was to determine frequency of transition of NYHA class III / IV to NYHA class I / II / III of stage C & D HF with drugs in a tertiary level hospital. Methods: This was a crosssectional study. A total of 45 patients with stage C and D HF were enrolled in the study by consecutive sampling from October 2019 to September 2020. Detailed history including NYHA functional class of stage C and D HF, physical examination, relevant investigations and Echocardiography were done in all the subjects. The subjects were treated accordingly. The treatment response was assessed again with NYHA functional class on discharge. Result: Patients had mean age of 62 &60 and 54 & 54 years for NYHA class III & IV of stage C and D HF. Majority of the patients were male. Primary cause of HF for both stage were IHD followed by DCM and valvular heart disease. The clinical presentation of stage C & D HF was improved significantly on discharge. Haematological, biochemical, radiological and echocardiographic findings of NYHA class IV of stage C & D HF was more worst. Conclusion: There is statistically significant transition of NYHA class III of stage C and D HF to lower NYHA class but there is no statistically significant transition of NYHA class IV of stage C and D HF with pharmacotherapy in a tertiary level hospital. Higher NYHA class is associated with poor outcome of stage C & D HF patients. University Heart Journal 2022; 18(1): 14-21